ADP Ribosylation Factor 6 (ARF6) Promotes Acrosomal Exocytosis by Modulating Lipid Turnover and Rab3A Activation - Pelletán, Leonardo E. (J Biol Chem, 2015)
Regulated secretion is a central issue for the specific function of many cells; for instance, mammalian sperm acrosomal exocytosis is essential for egg fertilization. ARF6 (ADP-ribosylation factor 6) is a small GTPase implicated in exocytosis, but its downstream effectors remain elusive in this process. We combined biochemical, functional, and microscopy-based methods to show that ARF6 is present in human sperm, localizes to the acrosomal region, and is required for calcium and diacylglycerol-induced exocytosis. Results from pulldown assays show that ARF6 exchanges GDP for GTP in sperm challenged with different exocytic stimuli. Myristoylated and guanosine 5′-3-O-(thio)triphosphate (GTPγS)-loaded ARF6 (active form) added to permeabilized sperm induces acrosome exocytosis even in the absence of extracellular calcium. We explore the ARF6 signaling cascade that promotes secretion. We demonstrate that ARF6 stimulates a sperm phospholipase D activity to produce phosphatidic acid and boosts the synthesis of phosphatidylinositol 4,5-bisphosphate. We present direct evidence showing that active ARF6 increases phospholipase C activity, causing phosphatidylinositol 4,5-bisphosphate hydrolysis and inositol 1,4,5-trisphosphate-dependent intra-acrosomal calcium release. We show that active ARF6 increases the exchange of GDP for GTP on Rab3A, a prerequisite for secretion. We propose that exocytic stimuli activate ARF6, which is required for acrosomal calcium efflux and the assembly of the membrane fusion machinery. This report highlights the physiological importance of ARF6 as a key factor for human sperm exocytosis and fertilization.